2015
DOI: 10.1155/2015/916585
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen: An Emerging Regulator of Insulin Action and Mitochondrial Function

Abstract: Clinical trials and animal studies have revealed that loss of circulating estrogen induces rapid changes in whole body metabolism, fat distribution, and insulin action. The metabolic effects of estrogen are mediated primarily by its receptor, estrogen receptor-α; however, the detailed understanding of its mechanisms is incomplete. Recent investigations suggest that estrogen receptor-α elicits the metabolic effects of estrogen by genomic, nongenomic, and mitochondrial mechanisms that regulate insulin signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 78 publications
7
107
0
10
Order By: Relevance
“…These two metabolic disorders are also reportedly associated with high miscarriage rates, decreased pregnancy rates, and low live birth rates. Some research has proven that ovariectomy in mice could cause an increased level of insulin [33,34]. The present study demonstrated that women with PCOS had lower serum FSH [18].…”
Section: Discussionsupporting
confidence: 53%
“…These two metabolic disorders are also reportedly associated with high miscarriage rates, decreased pregnancy rates, and low live birth rates. Some research has proven that ovariectomy in mice could cause an increased level of insulin [33,34]. The present study demonstrated that women with PCOS had lower serum FSH [18].…”
Section: Discussionsupporting
confidence: 53%
“…Specifically, studies suggest that males are more susceptible to obesity than females [5961]; the protection against obesity in females is attributed to the direct effects of the circulating estrogen levels on insulin/glucose homeostasis, body fat distribution and pro-inflammatory markers [62, 63]. Estrogen also downregulates hepatic lipogenesis [64, 65], which could be a potential reason for why the hepatic fat deposition (evidenced by the increased absolute liver weight) in our female mice was delayed and was observed only during the later stages of HFD intake.…”
Section: Discussionmentioning
confidence: 99%
“…44, 45 Postmenopausal women have altered metabolism manifested by increased abdominal adipose tissue and dyslipidemia. 46 Ovariectomized animals exhibit marked weight gain and dysregulated metabolic state, promptly reversed by E2 replacement.…”
Section: Estrogen and Ers In Cardiac Metabolismmentioning
confidence: 99%